2022
DOI: 10.3390/molecules27196249
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel c-Jun N-Terminal Kinase 1 Inhibitors from Natural Products: Integrating Artificial Intelligence with Structure-Based Virtual Screening and Biological Evaluation

Abstract: c-Jun N-terminal kinase 1 (JNK1) is currently considered a critical therapeutic target for type-2 diabetes. In recent years, there has been a great interest in naturopathic molecules, and the discovery of active ingredients from natural products for specific targets has received increasing attention. Based on the above background, this research aims to combine emerging Artificial Intelligence technologies with traditional Computer-Aided Drug Design methods to find natural products with JNK1 inhibitory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Fu [95] combined CNN with traditional algorithm models to analyze tonguecoating properties and found that the performance of the integrated model was improved. On the basis of the voting and stacking strategy, Yang [96] performed rule integration-model fusion on three machine learning models of SVM, RF, and neural network, and achieved good performance. Ge [97] proposed an ensemble algorithm that integrated the attention mechanism and LSTM, and showed that this ensemble algorithm can effectively select salient locations with higher accuracy and less computation.…”
Section: Advantages Of Algorithm Ensemble and Establishment Of Syndro...mentioning
confidence: 99%
“…Fu [95] combined CNN with traditional algorithm models to analyze tonguecoating properties and found that the performance of the integrated model was improved. On the basis of the voting and stacking strategy, Yang [96] performed rule integration-model fusion on three machine learning models of SVM, RF, and neural network, and achieved good performance. Ge [97] proposed an ensemble algorithm that integrated the attention mechanism and LSTM, and showed that this ensemble algorithm can effectively select salient locations with higher accuracy and less computation.…”
Section: Advantages Of Algorithm Ensemble and Establishment Of Syndro...mentioning
confidence: 99%